Multilevel associations of peer cognitive factors and adolescent cannabis use in a legal recreational cannabis region - Kenyon, Emily A.; Yang, Manshu; Chung, Tammy; Wilson, Anna C.; Feldstein Ewing, Sarah W. (Frontiers in Psychiatry, 2024)
BackgroundCannabis use can have unintended, harmful consequences for adolescents, a developmental group that struggles with heightened pressure to align with peer attitudes and behaviors. The role of social-cognitive factors in shifting cannabis use dynamics remains under explored, particularly in states where recreational cannabis use is legal.ObjectivesThe present study examined multilevel longitudinal associations between resistance to peer influence, peer norms, and adolescent cannabis use over the course of 12 months.MethodParticipants were N=204 adolescents ages 15-19 (Mage = 18.68; 67% female) recruited via community outreach after the legalization of adult (age 21+) recreational cannabis use in the Portland, Oregon metropolitan region. Eligible participants endorsed 1+ heavy episodic drinking (HED) episode in the prior two months. Data were collected across four timepoints over 12 months. Multilevel latent growth curve modeling investigated associations between time-varying cognitive factors (resistance to peer influence, peer norms) and two cannabis outcomes (hazardous use, past-month use).ResultsFindings showed individual increases in hazardous cannabis use over time were significantly associated with adolescents reporting higher peer norms (i.e., higher perceived prevalence and frequency of peer cannabis use) and lower resistance to peer influence. When assessing between-adolescent differences, hazardous cannabis use was only associated with peer norms. Individual variation over time and between-adolescent differences on past-month cannabis use was associated with peer norms, but not resistance to peer influence.ConclusionsEvolving cognitive factors like resistance to peer influence and peer norms may enhance understanding of longitudinal changes in hazardous cannabis use among adolescents and implicate helpful targets for prevention and intervention. It is a public health priority to identify factors that contribute to adolescent use trajectories in this period of growing cannabis legislation in order to guide the development of impactful prevention and intervention strategies.